The devil hath a pleasing shape - Roberts, Terry, 1956- (Roberts, Terry, 1956- Stephen Robbins chronicles., 2024)
"The autumn of 1924, and Benjamin Loftis has a problem. He is the manager of the glorious Grove Park Inn, the jewel in the crown of Asheville, North Carolina and of all the Southern mountains. This particular problem is in the form of a college girl who turns up one morning in one of his finest rooms -- naked and dead. Shot twice with a small caliber pistol. After weeks of increasingly bad publicity, Loftis calls in Stephen Robbins, a local man who is famous in some circles for finding missing people and solving unsolvable crimes. Robbins eventually solves the puzzle of who is killing Asheville's prostitutes. But when he does, he runs head on into the financial and political elite who control this mountain town, those who want a murderer caught and punished but not the murderer"--